A tall order on a tight timeframe: stakeholder perspectives on comparative effectiveness research using electronic clinical data. (September 2012) - Holve, Erin; Hamilton Lopez, Marianne; Scott, Lisa; Segal, Courtney
Background & significance: The AcademyHealth Electronic Data Methods Forum aims to advance the national dialogue on the use of electronic clinical data (ECD) for comparative effectiveness research (CER), patient-centered outcomes research, and quality improvement by facilitating exchange and collaboration among eleven research projects and external stakeholders. AcademyHealth conducted a mixed-method needs assessment with the Electronic Data Methods Forum's key stakeholders to assess: stakeholder views on developing new infrastructure for CER using ECD; current gaps in knowledge with respect to CER; and expectations for a learning health system.Methods: AcademyHealth conducted 50 stakeholder interviews between August 2011 and November 2011 with participants from the following seven stakeholder groups: government, business/payer, industry, healthcare delivery, patient/consumer, nonprofit/policy and research. With input from key collaborators, AcademyHealth designed a semi-structured interview guide and a short survey. Reviewers used the qualitative data analysis software NVivo to code the transcripts and to identify and manage complex concepts. Quantitative data from the questionnaire has been integrated with the final analysis as relevant.Results: The analysis of recurring concepts in the interviews focus on five central themes: stakeholders have substantial expectations for CER using ECD, both with respect to addressing the limitations of traditional research studies, and generating meaningful evidence for decision-making and improving patient outcomes; stakeholders are aware of many challenges related to implementing CER with ECD, including the need to develop appropriate governance, assess and manage data quality, and develop methods to address confounding in observational data; stakeholders continue to struggle to define 'patient-centeredness' in CER using ECD, adding complexity to attaining this goal; stakeholders express that improving translation and dissemination of CER, and how research can be 'useful' at the point of care, can help mitigate negative perceptions of the CER 'brand'; and stakeholders perceive a need for a substantial 'culture shift' to facilitate collaborative science and new ways of conducting biomedical and outcomes research. Many stakeholders proposed approaches or solutions they felt might address the challenges identified.